Improvement in sprint start performance by modulating an initial loading location on the starting blocks - Nagahara, R.; Gleadhill, S.; Ohshima, Y. (Journal of Sports Sciences, 2020)
This study examined whether modulation of the centre of pressure (COP) on the starting block surface would improve sprint start performance. Twenty male national-level sprinters performed 15-m sprints from the starting blocks in three different conditions (normal, anterior loading and posterior loading), during which ground reaction forces (GRFs) were recorded. The COP location, 10-m time, average horizontal external power (AHEP), spatiotemporal and GRF variables were calculated. The results demonstrate that, although modulation of COP location may not improve sprint start performance for the entire group, it could improve the corresponding performance for specific individuals. A sprinter who favours the posterior front block location and more to the posterior rear block COP location on the block surface at the set position could possibly improve AHEP using the anterior loading condition. An improvement of AHEP in the anterior loading condition (p =.056, effect size [ES] =.305) would be accomplished by greater rear block anteroposterior mean force (p =.043, ES =.574). Moreover, the posterior loading condition may improve the 10-m time and/or AHEP for some individuals, whereas no specific characteristics of the individuals were found. Finally, an improvement of 10-m time in the posterior loading condition (p =.015, ES =.609) would be accomplished by shorter reaction time (p =.035, ES =.780).